2022
DOI: 10.5723/kjcs.2022.43.3.201
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Preschool Teachers’ Adaptability on Burnout Through Digital Literacy and Teaching Efficacy During the Covid-19 Pandemic: The Role of the On-line Teaching Experience

Abstract: Objectives: This study examines the extent to which preschool teachers’ adaptability influences their burnout, focusing on the double mediating effects of digital literacy and teaching efficacy during the COVID-19 pandemic, and whether such effects are influenced by online teaching experiences. It aims to highlight the importance of teachers’ adaptability and digital literacy as protective factors in preventing burnout in situations of crisis or future virtual education environments.Methods: A total of 222 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Teachers who demonstrated high adaptability in unforeseen circumstances experienced reduced burnout in their profession. Further, correlational findings showed that those who exhibited high adaptability also upheld high levels of teaching efficacy and digital utilization for instruction, both of which were linked to decreased burnout levels (Kim et al, 2022).…”
Section: Importance Of Teaching Adaptability For Ece Teachers During ...mentioning
confidence: 97%
See 1 more Smart Citation
“…Teachers who demonstrated high adaptability in unforeseen circumstances experienced reduced burnout in their profession. Further, correlational findings showed that those who exhibited high adaptability also upheld high levels of teaching efficacy and digital utilization for instruction, both of which were linked to decreased burnout levels (Kim et al, 2022).…”
Section: Importance Of Teaching Adaptability For Ece Teachers During ...mentioning
confidence: 97%
“…Another study among secondary teachers found that teachers' adaptability was linked to greater well-being and greater commitment to the school, as well as increased student achievement in numeracy (Collie and Martin, 2017). For ECE teachers, their teaching adaptability was positively correlated with their digital literacy and efficacy, and negatively correlated with job burnout (Kim et al, 2022). Indeed, adaptability is considered as a personal resource that contributes to individuals' success in and satisfaction with their jobs (Collie and Martin, 2017).…”
Section: Importance Of Teaching Adaptability For Ece Teachers During ...mentioning
confidence: 99%
“…Burnout is defined as "emotional exhaustion, depersonalization and reduced personal sense of accomplishment" [36]. In the study that involved 47 teachers from 18 countries [17], researchers raised concerns that the level of teacher burnout had increased during the COVID-19 pandemic [35]. It was discovered that the participants had experienced burnout in four main dimensions, namely psychological (e.g., stress and anxiety), health-related (e.g., aching eyes, insomnia), and physical-state related (e.g., lack of energy) and educational (e.g., lack of resources and face-to-face contact, increased workload).…”
Section: The Effect Of Communication Technology On Teacher-student Re...mentioning
confidence: 99%